The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1302/0301-620x.85b1.13300
|View full text |Cite
|
Sign up to set email alerts
|

Role of posterior stabilisation in the management of tuberculosis of the dorsal and lumbar spine

Abstract: We present a prospective study of patients with tuberculosis of the dorsal, dorsolumbar and lumbar spine after combined anterior (radical debridement and anterior fusion) and posterior (instrumentation and fusion) surgery. The object was to study the progress of interbody union, the extent of correction of the kyphosis and its maintenance with early mobilisation, and the incidence of graft and implant-related problems. The American Spinal Injury Association (ASIA) score was used to assess the neurological stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
98
0
6

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(111 citation statements)
references
References 10 publications
7
98
0
6
Order By: Relevance
“…Expandable cages have the advantage of a primary stable anchorage and avoidance of the donor site morbidity that occurs with structural autologous bone graft harvesting. Both the present study and studies by other authors have demonstrated that the use of metallic implants in an infected area of the spine does not lead to persistence or recurrence of the infection [4,8,19,21]. In addition to stabilisation of the spine, the good perfusion of the vertebral bodies and adequate soft tissue coverage of the anterior thoracolumbar spine (including immunologically active structures such as the peritoneum) are regarded as the main factors contributing to the success of this technique [4,12].…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…Expandable cages have the advantage of a primary stable anchorage and avoidance of the donor site morbidity that occurs with structural autologous bone graft harvesting. Both the present study and studies by other authors have demonstrated that the use of metallic implants in an infected area of the spine does not lead to persistence or recurrence of the infection [4,8,19,21]. In addition to stabilisation of the spine, the good perfusion of the vertebral bodies and adequate soft tissue coverage of the anterior thoracolumbar spine (including immunologically active structures such as the peritoneum) are regarded as the main factors contributing to the success of this technique [4,12].…”
Section: Discussionsupporting
confidence: 60%
“…However, an increasing number of studies advocate a combination of posterior stabilisation and anterior debridement and interbody fusion. The advantages of this technique are better correction of the kyphotic deformity and its maintenance, and earlier patient mobilisation [1,5,7,8,11,14,15,19].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Metal implants were considered to hinder healing of the infections with increased rates of septic loosening [15,16]. Indeed, extensive clinical and surgical studies uphold the choice of synthetic material implantation during the acute infective phase of vertebral osteomyelitis [13].…”
Section: Epidemiology and Surgical Indicationsmentioning
confidence: 99%